The Legal Status of Private Joint Stock Company Shares upon their Conversion to Public Joint Stock Company: An Analytical Study in the Jordanian Company Law - Alomar, Adnan; Alnaimi, Jamal (Dirasat: Shari’a and Law Sciences, 2023)
Objectives: The study aimed to demonstrate the extent to which the shares of a private joint stock company are affected upon conversion to a public joint stock company, where the latter is subject to a different legal framework in terms of its structure, shares, and methods of capital accumulation. Methods: This study adopted a descriptive approach with two aspects: analytical of the company law texts and related legislations, and practical in terms of judicial provisions. The study was divided into two main requirements: the first investigates the impact of conversion on the general characteristics of the company’s capital and shares, and the second investigates the impact of conversion on the characteristics of each type of shares in the private joint stock company. Results: The results showed that the conversion of a private joint stock company to a public joint stock company requires changes in its capital provisions, and it subjects its shares to the principle of legal regulation, after being governed by the principle of freedom of will. Moreover, as a result of the conversion, the privileges of the shares, their redeem ability, their categories, types, and nominal values disappear, to become a single type, namely common shares. In addition, this conversion does not prevent the founders of the converted company from selling their shares immediately after their listing on the stock market. Conclusion: The study conclude that the conversion process affects the provisions of the converted company, particularly in terms of its capital, shares, privileges, and the partners’ freedom to sell their shares. It is necessary for the Jordanian legislator to issue special instructions regarding treasury shares, as well as for the listing and trading of securities issued by the private joint stock company.